Hands-On UX Design for Developers : Design, Prototype, and Implement Compelling User Experiences from Scratch. - Canziba, Elvis (Packt Publishing Ltd, 2018)
This hands-on guide will teach you simple-to-advanced steps of user experience design. It starts from idea concept evaluation, product research, user interface design, and design implementation in code. We focus not only on the UI or design, but also on other things that are connected to it. UX has its own process that requires its own sets of ...